1997
DOI: 10.1097/00005392-199707000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Change of Bladder Hypertrophy Due to Benign Prostatic Hyperplasia After Surgical Relief of Obstruction

Abstract: Bladder hypertrophy was completely reversible after the surgical treatment of the obstruction in the majority of patients with BPH. The measurement of ultrasound estimated bladder weight was of value in monitoring therapeutic effects in BPH patients. An extraordinarily high ultrasound estimated bladder weight of 80 gm. or more might suggest degenerative and irreversible pathological changes in the bladder detrusor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 17 publications
4
32
0
1
Order By: Relevance
“…Even after relief of obstruction, the changed bladder may not return to its original state before obstruction, and this might result in remaining symptoms (35). For example, Kojima et al (17) showed that their patients with a high ultrasoundestimated bladder weight above the fixed level of 80 g were characterized by irreversible pathological changes in the detrusor.…”
Section: Discussionmentioning
confidence: 99%
“…Even after relief of obstruction, the changed bladder may not return to its original state before obstruction, and this might result in remaining symptoms (35). For example, Kojima et al (17) showed that their patients with a high ultrasoundestimated bladder weight above the fixed level of 80 g were characterized by irreversible pathological changes in the detrusor.…”
Section: Discussionmentioning
confidence: 99%
“…UEBW significantly decreased from 52.9±22.6 g to 31.6±15.8 g (р<0.0001) in approximately 33 patients 12-weeks post-prostatectomy. [18] However, the assumption that the bladder has a spherical configuration appears to be unrealistic.…”
Section: Ultrasound Estimated Bladder Weightmentioning
confidence: 99%
“…19 Interestingly, there was no difference between the 3 time-groups in our study regarding the postoperative need of chronic clean intermittent catheterization -consistent with a report by Kojima and colleagues on the reversibility of detrusor muscle changes after relief of outflow obstruction. 20 Longer medical treatment for BPH has been associated with a decreased number of patients undergoing BPH surgery resulting in increased prostate volume with potentially more patients needing open surgery. 21 The question is whether changes in laser surgery over the past 16 years have been able to sustain surgical outcome despite significant changes in the target population.…”
mentioning
confidence: 99%